Penguatan Karakter Profil Pelajar Pancasila melalui Pembelajaran Interaktif Berbasis Proyek Pembuatan Foto dan Video - Utami, Citra Dewi; Noorva Yudhitya, Roudlotul Jannati Rochnadia; Nugroho, Widhi (Abdi Seni, 2023)
Character building is one of the biggest challenges for the education system in Indonesia from time to time. The Ministry of Education launched a Merdeka Curriculum with the “Proyek Penguatan Profil Pelajar Pancasila” (P5) or A Project of Strengthening Pancasila-Student Profile as the main activity to address the issue. However, several schools find it challenging to implement the program because they encounter obstacles and still need assistantships. This community service aims to assist schools not belonging to Sekolah Penggerak in organizing P5 through interactive learning projects that create photos and videos. Data collection was carried out using the method of observation, interviews, and literature study. The results obtained identify project implementation processes suitable for strengthening student character in the dimensions of independence, mutual cooperation, critical reasoning, and creativity. This Community Service Program is considered successful in assisting the implementation of P5 through the level of satisfaction conveyed by teachers and students as project implementers.